The Effect of Different Types of Mechanical Filters in the Recirculation System on the Growth and Survival rates of Tilapia (Oreochromis niloticus) - Rahmawati, Aulia; Sianturi, Andre Soaloon; Yuniarti, Ating; Supriatin, Febriyani Eka (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2025)
Tilapia is one of the leading fishery commodities with high market demand. Therefore, the productivity of tilapia cultivation for consumption must be driven intensively. The aim of this research is to evaluate which types of mechanical filters are best for recirculation systems and the survival rate of tilapia fish. The research was carried out for 30 days at the Fish Reproduction Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Brawijaya, Malang. The experimental method used was a completely randomized design. With coconut fiber, dacron and gravel treatment. The main parameters observed were survival rate (SR), specific growth rate (SGR), absolute weight gain, total dissolved solid (TDS), and total suspended solid (TSS). For supporting parameters such as pH, temperature of dissolved oxygen (DO) and ammonia. From the results of the research that has been carried out, it can be seen that the use of different filter media for rearing red tilapia (Oreochromis niloticus) in fresh water using a recirculation system has an influence on absolute weight growth, specific growth rate and survival rate. The research data obtained was that the dacron filter had an absolute weight growth of 4,46 g, TDS 348 mg/L, TSS 7,25 mg/L, pH 7,55, temperature 25,5 °C, DO 7,41 ppm and ammonia 0,017 ppm. Coconut fiber absolute weight 4,46 g, TDS 374 mg/L, TSS 7,25 mg/L, pH 7,69, temperature 25,2 °C, DO 7,52 ppm and ammonia 0,014 ppm. Gravel absolute weight 3,87 g, TDS 387,5 mg/L, TSS 8,25 mg/L, pH 8,33, temperature 25,2 °C, DO 7,52 ppm and ammonia 0,014 ppm